Hue shifts produced by temporal asymmetries in chromatic signals - Stockman, A; Henning, G; West, P; Rider, A; Smithson, H; Ripamonti, C (Association for Research in Vision and Ophthalmology, 2017)
Observers viewed M- or L-cone-isolating stimuli and compared slowly-on and slowly-off sawtooth waveforms of the same mean chromaticity and luminance. Between 6 and 13 Hz, the mean hue of slowly-on L-cone and slowly-off M-cone sawtooth flicker appeared redder, and the mean hue of slowly-off L-cone and slowly-on M-cone sawtooth stimuli appeared greener—despite all the waveforms' having the same mean, near-yellow-appearing chromaticity. We measured the effect of the modulation depth and the slope of the sawtooth on the mean hue shifts as a function of temporal frequency. The results are complex but show that discriminability depended mainly on the second harmonic of the waveforms. We considered several models with combinations of linear and nonlinear stages. First, we considered models in which a nonlinear stage limits the rate of change of hue and restricts the steep slope of the sawtooth waveform more than its shallow slope, thus shifting the mean hue in the direction of the shallower slope (such a nonlinearity is also known as a slew-rate limit). Second, we considered saturation models in which the nonlinear stage compresses hue signals and thus shifts the mean of asymmetrical waveforms with or without differentiation before the nonlinearity. Overall, our modeling and results suggest that the hue shift occurs at some nonlinear mechanism in the chromatic pathway; and that, in terms of the Fourier components of the various waveforms, the effect of the nonlinearity depends crucially on the timing of the second harmonic relative to the first.